Effect of Collaborative Based Inquiry Learning Model Using Macromedia Flash and Motivation on Science Learning Outcomes of 5th Grade Students of Elementary School Angkasa 2 Lanud Soewondo Medan - Wanty Astari; Retno Dwi Suyanti; Daulat Saragi (BIRCU, 2021)
This study aims to determine the differences in learning outcomes with the use of guided inquiry learning models using collaborative-based macromedia flash and based on children's learning motivation attitudes, as well as the interaction between the two models with the level of children's learning motivation in influencing student learning outcomes improvement. The research was conducted at SD Angkasa 2 LANUD Medan in the even semester of the 2020/2021 school year. The sample in this study consisted of classes V-A and V-B which were taken by purposive sampling class. Class V-A is an experimental class that is taught using the guided inquiry learning model using collaborative-based macromedia flash, while for the control class, it is taught using the selected direct learning model, class V-B. This means that student learning outcomes with the guided inquiry learning model using collaborative-based macromedia flash is better than direct learning. Acquisition of calculated F value of 5,123 is greater than the F table of 4,001, with a significance value of 0.027 <0.05. This means that the learning outcomes of students with high learning motivation are better than students with low learning motivation, and the calculated F value of 0.189 is smaller than the F table, namely 4.001 with a significance value of 0.665> 0.05, then H0 is accepted and Ha is rejected, so in the study There is no interaction between learning motivation in the application of the guided inquiry learning model using collaborative-based macromedia flash or direct learning on student learning outcomes. This study shows that the learning model and learning motivation do not influence and reject the third hypothesis.